2017
DOI: 10.1007/s11746-017-3014-y
|View full text |Cite
|
Sign up to set email alerts
|

Sonocrystallization of Interesterified Fats with 20 and 30% of Stearic Acid at the sn‐2 Position and Their Physical Blends

Abstract: Physical blends (PB) of high oleic sunflower oil and tristearin with 20 and 30% stearic acid and their interesterified (IE) products where 20 and 30% of the fatty acids are stearic acid at the sn‐2 position crystallized without and with application of high intensity ultrasound (HIU). IE samples were crystallized at supercooling temperatures (ΔT) of 12, 9, 6, and 3 °C while PB were crystallized at ΔT = 12 °C. HIU induced crystallization in PB samples, but not in the IE ones. Induction in crystallization with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 21 publications
7
38
0
Order By: Relevance
“…This behavior might be related to the MG crystallization process, which occurred slower at 0.1 °C/min compared to the samples that were cooled at 10 °C/min. Previous studies have demonstrated that an induction in the crystallization of lipids takes place when the driving force increases, and this increment can be achieved either through higher supersaturation or supercooling levels (Kadamne et al., , ; Lee et al., ). These studies have also shown that HIU is not effective at inducing crystallization if the content of saturated fatty acids is too low (lower degree of supersaturation), corroborating the lack of effect of HIU on hardness for low MG concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior might be related to the MG crystallization process, which occurred slower at 0.1 °C/min compared to the samples that were cooled at 10 °C/min. Previous studies have demonstrated that an induction in the crystallization of lipids takes place when the driving force increases, and this increment can be achieved either through higher supersaturation or supercooling levels (Kadamne et al., , ; Lee et al., ). These studies have also shown that HIU is not effective at inducing crystallization if the content of saturated fatty acids is too low (lower degree of supersaturation), corroborating the lack of effect of HIU on hardness for low MG concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, SFC increased in OG3 and OG4.5 sonicated samples obtained at 0.1°C/min, whereas it decreased in OG 4.5 sonicated samples obtained at 10°C/min. Previous studies performed in triacylglycerols have shown that HIU is more efficient at inducing crystallization and changing physical properties in samples with a slow crystallization kinetics (Kadamne et al, 2017a;Kadamne, Ifeduba, Akoh, & Martini, 2017b). Slower crystallization kinetics can be obtained, for example, by either working at a low driving force, or by using slow cooling rates.…”
Section: Solid Fat Contentmentioning
confidence: 99%
“…Acoustic cavitation is the main phenomenon responsible for inducing nucleation (Suzuki et al, ) and secondary crystallization (Ye et al, ) in sonicated samples (Lauterborn et al, ). In combination with supercooling and agitation, HIU can reduce the induction period of crystallization (Martini, Bertoli, Herrera, Neeson, & Marangoni, ), increase the solid fat content (SFC) (Kadamne, Ifeduba, Akoh, & Martini, ), increase the hardness (Suzuki et al, ), viscosity, and viscoelasticity (Kadamne et al, , ; Ye et al, ), and can generate small crystals (Kadamne et al, , ; Suzuki et al, ; Ye et al, ) and stable polymorphs (Ueno, Ristic, Higaki, & Sato, ) in the system. In lieu of these HIU‐induced changes, sonication appears to be an efficient way to tailor low‐saturated fats and lower melting point fats for use as trans fat alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…However, these fats were too soft for food use. Kadamne et al () studied the crystallization behavior and properties of these fats under nonsonicated and sonicated conditions at different supercooling levels. The authors found that HIU was most effective in increasing the rate of crystallization at the lowest supercooling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation